Epidemiological and genetic characteristics of enteroviruses associated with hand, foot, and mouth disease in Jiaxing, China from 2019 to 2022 - Shencong Lv; Yamei Zhou; Jimei Ji; Yong Yan; Guoying Zhu (Scientific Reports)
Abstract Hand, foot, and mouth disease (HFMD) is mainly caused by enteroviruses (EVs) and represents an important public health problem in China. The aim of this study was to investigate the epidemiological and genetic characteristics of EVs associated with HFMD in Jiaxing City in 2019–2022. In total, 1807 clinical specimens collected from patients with HFMD were evaluated by real-time reverse transcription polymerase chain reaction, and 1553 EV-positive specimens were detected, including 1018 coxsackievirus A6 (CVA6), 301 coxsackievirus A16 (CVA16), 94 coxsackievirus A10 (CVA10), 7 enterovirus A71 (EV-A71), and 133 other EVs. A phylogenetic analysis revealed that the subgenogroups CVA6 D3a, CVA10 F, and CVA16 B1a B1b were predominant in Jiaxing. Compared with VP1 of the prototype strains of CVA6, CVA10, and CVA16, 34, 36, and 31 amino acid substitutions were detected, respectively. Children aged 1–5 years accounted for the majority of cases, and the infection rate was higher in males than in females. EV infection cases were clearly affected by the COVID-19 epidemic, with decreases in 2020 corresponding to the implementation of protective measures. These findings add to the global genetic resources for EVs and demonstrate the epidemiological characteristics and genetic features of HFMD in Jiaxing.